PEMBERDAYAAN UMKM KERUPUK SINGKONG MELALUI PEMBINAAN KEWIRAUSAHAAN DAN PENINGKATAN KESADARAN HUKUM PERLINDUNGAN KONSUMEN - Rachmawati Rachmawati; Afra Roki; Tiza Yaniza (Jurnal Abdimas Bina Bangsa, 2024)
The purpose of this activity is to empower cassava cracker MSMEs through entrepreneurship coaching and increasing awareness of consumer protection laws. The method of implementing activities is legal counseling and technical training on product packaging in accordance with the provisions of laws and regulations as well as increasing the production capacity of household businesses. The obligation to meet food packaging standards in order to realize safe food products is closely related to the obligation to label food. This PKM activity is an effort to empower MSME business actors in their food production. In order for these MSME business actors to be able to produce and package food according to food packaging and labeling standards, training in packaging and making food labels in accordance with regulations is given. In addition, MSME actors are also given equipment assistance that can support and increase production, but still by paying attention to statutory provisions. In the future, it is expected that more MSME business actors will have legal awareness about food packaging and labels in carrying out their business activities. For example, with the sustainability of PKM activities using the same model, but applied to different MSMEs, it can even be expanded again with MSMEs in other areas outside Kubu Raya Regency. It is also necessary to include other related parties, such as business groups, credit unions, banks, and local governments, so that the scope of benefits of activities can be wider